Hidden defaults - Sebastian Horn; Carmen M. Reinhart; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2022)
China's lending boom to developing countries is morphing into defaults and debt distress. Given the secrecy surrounding China's loans, also the associated defaults remain 'hidden', as missed payments and restructuring details are not disclosed. We construct an encompassing dataset of sovereign debt restructurings with Chinese lenders and find that these credit events are surprisingly frequent, exceeding the number of sovereign bond or Paris Club restructurings. Chinese lenders follow a resolution approach reminiscent of 1980s Western lenders; they seldom provide deep debt relief with face value reduction. If history is any guide, multi-year debt workouts with serial restructurings lie in store.
Keywords: F21; F34; F42; F6; G15; H63; N25; 330; China; external debt; default; crisis resolution; official lending; hidden debts; sovereign risk; Belt and Road initiative